A crise da autoridade jurídica e o terrorismo como forma de comunicação de poder: direito e poder na pós-modernidade - Andrade, Diogo Thomson de (2009)
This work proposes to the study of the relationship between law and power in the contemporary context, which we named post-modernity. Thus, through the analysis on the crisis of legitimacy that affects the power and law within the nation state, evidenced by the constant attack of terrorism on existing orders, we address the various issues involving the constitution and evolution of the modern state and the changes that are occurring in the contemporary world, to reframe the relationship between law and power in order to be more appropriate to the post-modernity context. For doing that, we have studied political theory and sociology in order to address the issue the relation of power and law in modernity and post modernity, and at the same time, the legal theories arising from that. Furthermore, by means of an approximation within the theory of communication, we´ve tried to refresh the study of the relationship between law and power. In the end, we propose, based on the results obtained in the reflection, how the legal authority can be reinterpreted to obtain the material to achieve legitimacy in the post-modern